Evaluation of operational efficiency of the national anti-malaria program in "High-Risk" rural areas of Vadodara district - Solanki D; Misra Shobha (Wolters Kluwer Medknow Publications, 2007)
Background: Malaria was and is a major scourge in India contributing more than three-fourths of the total cases in the Southeast Asian (SEA) region. Malaria is largely infl uenced by the local environmental conditions but can be kept in check if the operational implementation of the National Antimalaria Program: (NAMP) is effective. Keeping in mind the context of the situation in Gujarat, there was an urgent need to carry out a study to assess the operational aspects of the ongoing malaria control program. Objectives: To assess the operational aspects of NAMP in "highrisk" areas of rural Vadodara, seeking bottlenecks and possible correlation to the malaria situation in those areas. Materials and Methods: From 269 "high-risk" villages, 20 villages were selected randomly from 10 Talukas. 40 slide (smear-)-negative, 19 slide (smear-)-positive, 10 laboratory technicians, 10 MultiPurpose Workers (MPW) Supervisors and 18 MultiPurpose (MPW) and 18 Voluntary Workers were interviewed. The performance of the malaria clinic and the NAMP staff was evaluated using a point system. Results and Conclusions: The monthly blood examination rate (MBER) targets could not be achieved in 8 out of 10 primary health centers (PHCs) by active surveillance workers (AS) workers. The mean time interval between blood smear collection (BSC) and its receipt in the laboratory was 7.1 days. 46% of smear-negative patients having received presumptive treatment (PT) and 22% of smear-positive patients receiving radical treatment (RT) were supervised. Administration of "adequate" presumptive treatment and radical treatment to the above two sets of individuals was 65% and 58% respectively. Overall, the performance of 50% of malaria clinics and 94% of villages was poor to average. The study has found enough evidence to conclude that there were lapses in the operation of the NAMP.